KORUPSI: TEORI, FAKTOR PENYEBAB, DAMPAK, DAN PENANGANANNYA - Ola Rongan Wilhelmus (Bahasa Indonesia, 2017)
Corruption is against the law and abuse of authority for the sake of self-enrichment, a group of people or corporations. Transparency International institutions 2015 and 2016 have placed Indonesia as one of the most corrupt countries in the world. Corruption in Indonesia has a very bad impact on various dimensions of society and nation life and can damage the economic system, democracy, politics, law, government and others. Although corruption is already so great, efforts to combat corruption have not shown optimal results. Seeing the difficulties of eradicating corruption, there needs to be a more serious and radical effort in the future to combat corruption in Indonesia, among others through: reforming political institutions, reforming the bureaucracy, formulating and implementing political ethical standards, enforcement that can give deterrent effect to corruptors , And the proper handling of corruption complaints procedures by the public.